HUBUNGAN ANTARA IKLIM KOMUNIKASI ORGANISASI DENGAN KINERJA KARYAWAN DINAS KOMUNIKASI DAN INFORMATIKA JAWA BARAT - Syifa Sharifa Rahmadani; Kokom Komariah; Hanny Hafiar (Universitas Prof. Dr. Moestopo (Beragama), 2022)
In a company, it is vital to understand the organizational climate which affects the achievement of organizational goals. This background encourages researchers to examine the relationship between organizational communication climate and employee performance at the West Java Communication and Information Office. Through a quantitative correlational study with a sample of 62 people. This study aims to determine the relationship between the trust of all members of the organization, joint decision-making, honesty, openness in downward communication, listening in upward communication, and attention to high-performance goals with functional tasks and behavioural tasks of the Java Communications and Informatics Service employees. West. The method used in this research is a quantitative correlational study. The results showed that all aspects of the organizational communication climate, including trust, shared decision making, honesty, openness in downward communication, listening in upward communication, and attention to high-performance goals, were significantly correlated with employee performance, including the following aspects: tasks functional and behavioural tasks. The highest correlation coefficient value is in the honesty aspect, with rs of 0.766. And the lowest correlation coefficient on the aspect of trust with rs of 0.303. The conclusion is that there is a significant relationship with a significant relationship between organizational communication climate and the performance of employees of the West Java Information and Communications Office.